Event‐based high throughput computing: A series of case studies on a massively parallel softcore machine. Issue 1 (19th December 2022) - Vousden, Mark; Morris, Jordan; McLachlan Bragg, Graeme; Beaumont, Jonathan; Rafiev, Ashur; Luk, Wayne; Thomas, David; Brown, Andrew
Abstract: This paper introduces an event‐based computing paradigm, where workers only perform computation in response to external stimuli (events). This approach is best employed on hardware with many thousands of smaller compute cores with a fast, low‐latency interconnect, as opposed to traditional computers with fewer and faster cores. Event‐based computing is timely because it provides an alternative to traditional big computing, which suffers from immense infrastructural and power costs. This paper presents four case study applications, where an event‐based computing approach finds solutions to orders of magnitude more quickly than the equivalent traditional big compute approach, including problems in computational chemistry and condensed matter physics. Abstract : This paper introduces an event‐based computing paradigm, where workers only perform computation in response to external stimuli (events) – this is best employed on the dedicated hardware. Event‐based computing is timely because it provides an alternative to traditional big computing, which suffers from immense infrastructural and power costs. This paper also shows how event‐based computing has been employed to solve certain computing problems orders of magnitude more quickly than the equivalent traditional big computing approach.